Dynamics of size-age structure of Notothenia rossii rossii at the shelf of the Kerguelen Islands. - Tankevich, P.B. (1994)
The dynamics of the length-age structure and of the recruits/parents stock ratio of the marbled rockcod Notothenia rossi the Kerguelen Isles (Southern Indian Ocean, France) from the start of the fishery in 1970 to the year 1991 were analysed. In the early years of the fishery (before 1973), the recruits constituted up to 20% of the catch, the remainder consisting of the mature fish. This ratio between the recruitment and the parent population reflected the length-age structure of the virgin stock. In the subsequent years, the share of mature fish in the catch considerably decreased as a result of intensive fishing (up to 150,000 t), which had negative effect on the level recruitment. For several years (1981-1985) only recruit-stock supported the fishery. Since 1985, the marbled rockcod has been taken only as a by-catch (no more than 240 tons annually) in fisheries for other target species, mainly the mackerel icefish (Champsocephalis gunnari). As a consequences of the protection measures by the French Administration, there has been a steady upward trend in average age and length of marbled rockcod in recent years. An analysis of the material collected during May-June 1991 showed that the length and age groups distribution pattern of the marbled rockcod as well as the ratio 'recruits/adults' were close to the corresponding indices for the population during the initial period of exploitation. An analysis of the materials on length-age composition of catches indicates that in 1991 the mature fish accounted for about 70%, which implies that the length-age structure of the virgin stock. Further banning on marbled rockcod fishery may result in natural mortality increasing owing to the considerable growth in the proportion of older fish. For the rational utilisation of the marbled rockcod stock, the fishery for older fish was proposed. Fishing for N. rossi in a limited scale allow to control the length-age structure of the population. По материалам исследований последних лет размерно-возрастной состав уловов заметно ...